The Effect of Work Discipline, Work Motivation and Organizational Culture on Employee Performance Improvement Strategies at Bogor City Hospital in 2024 - Qoyimah, Dillah Lidinil; Yuhelmis, Yuhelmis (International Journal of Social and Management Studies, 2024)
Research This done for know whether Discipline Work, Motivation Work and Culture Existing organizations​ capable give influence towards the improvement strategy performance employees at Bogor City Hospital This research use method Descriptive Quantitative involving 66 respondents​ non-medical employees at Bogor City Hospital. From the results data processing found r count > r table and t count > t table and seen from the significance produced it is <0.005 then This means that H0 is rejected and Ha is accepted. or Variables Independent influential to Variables Dependent. Discipline Work, Motivation Work and Culture Organization become something that is certainly very important because of with existence If Discipline Work, Motivation Work and Culture Organization applied so will become positive influence, result​ or the impact of course positive to existing employees.